Cancer risks in carriers of the BRCA1/2 Ashkenazi founder mutations. Issue 7 (16th February 2007) - Kadouri, Luna; Hubert, Ayala; Rotenberg, Yakir; Hamburger, Tamar; Sagi, Michal; Nechushtan, Chovav; Abeliovich, Dvorah; Peretz, Tamar
Abstract : Background: The risks for cancers other than breast (BC) or ovarian (OC) cancer in breast cancer gene 1 and 2 ( BRCA1/2 ) mutation carriers were elevated in studies of carrier families. However, case–control studies did not confirm this observation. Objective: To compare the risks for other cancers in BRCA1/2 mutation carriers and non-carriers, all affected with BC and/or OC. Both groups share risk modifiers of BC/OC, which enabled assessment of the role of BRCA1/2 mutations. Methods: 1098 Ashkenazi Jewish women affected with BC and/or OC were ascertained during 1995–2003; molecular testing revealed 229 BRCA1 and 100 BRCA2 carriers and 769 non-carriers. COX proportional hazard models were used to evaluate the risk of other cancers. Analyses were conducted including all other cancers or only those diagnosed after BC/OC diagnosis. Results: The HRs for any other cancer were 2.6 (95% CI 1.7 to 4.2, p<0.001) and 1.8 (95% CI 0.95 to 3.6, p = 0.07) in BRCA1 and BRCA2 carriers, respectively. The corresponding colon cancer HRs were 3.9 (95% CI 1.3 to 12.1, p = 0.02) and 2.3 (95% CI 0.5 to 11.3, p = 0.3) in BRCA1 and BRCA2 carriers. The HR for lymphoma was 11.9 (95% CI 3.1 to 46.2, p = 0.001) in BRCA2 carriers. Risk estimates for other cancers after the onset of BC/OC were similar. Conclusion: A 2.5-fold increase in any other cancer and a fourfold risk of colon cancer were found among BRCA1 carriers. The corresponding HRs in BRCA2 carriers were non-significant, except for the markedly elevated risk of lymphoma. These results suggest a role for BRCA1/2 mutations in colorectal cancer risk in a subgroup of BC/OC-affected carriers.